Family economic education as a strategy to mitigate the negative impact of online loan fintech in Sukosari Village, Lumajang Regency - Jayatri, Fidyah; Putri, Dwi Yanuarindah; Wildad, Sri Wahyuni (International Journal of Advances in Educational Research, 2025)
The rapid development of financial technology in today's digital era has brought significant changes to Indonesian society, including residents of Sukosari Village, Kunir Sub-district, Lumajang Regency, in how they conduct financial transactions. However, a lack of financial literacy has led to increasingly harmful consequences over time. This study aims to analyze how family-based economic education can be implemented to counteract the negative impacts of financial technology. This qualitative research employs a phenomenological approach, with 25 local residents as informants. The findings reveal that impulsive use of online loan fintech is driven by curiosity, the urge to experiment, and the appeal of convenient technology in meeting both needs and wants. Awareness of the risks typically arises only after the negative consequences have become significant. Family economic education plays a crucial role in curbing excessive use of online loan applications by fostering financial discipline through modeling and daily financial habits. However, this education can be undermined by internal individual factors, such as strong curiosity and a tendency to experiment without sufficient economic understanding.